DEVELOPMENT COST ESTIMATION STUDY SOLAR POWER PLANT (PLTS) IN DUSUN MOLO VILLAGE SEREN SELIMBAU BENGKAYANG DISTRICT - Santo, Eduardus; Husin, Fitriah; Arsyad, Muhammad Iqbal (Faculty of Engineering, Universitas Tanjungpura, 2024)
Currently, the use of energy sources as fuel for power plants still heavily relies on fossil fuels or, in other words, non-renewable energy sources that will gradually deplete and undoubtedly have environmental consequences. This research is conducted in an area that is geographically distant from the PLN (State Electricity Company) grid. Recognizing the need for increased use of Renewable Energy (EBT) and in line with the national target for 2025 set by the Ministry of Energy and Mineral Resources (ESDM), it is expected that the use of EBT can reach 23%. One of the efforts in developing EBT in areas that are not covered by the PLN electricity network is through Solar Power Plants (PLTS). The objectives of the upcoming research include calculating the cost per kilowatt (kW), determining the investment cost for the planned PLTS, and assessing the PLTS capacity to meet the energy demand in Dusun Molo, Bengkayang Regency. Based on the calculation results, the estimated daily electricity demand in Dusun Molo, Seren Selimbau Village, supplied by the PLTS, is 224,223 kWh/day. The power generated by the PLTS to meet the needs of Dusun Molo is 53,283 Wattpeak, while the planned power generation by the PLTS to meet Dusun Molo's requirements is 76,000 Wattpeak. The investment cost for the construction of the PLTS in Dusun Molo is IDR 3,213,751,000, including an 11% Value Added Tax (VAT). After the calculations, the Cost of Energy (COE) or price is determined to be IDR 2,972.00/kWh. This research provides an estimate of the investment cost for the construction of a PLTS in Dusun Molo, Bengkayang Regency.